Исследования на территории Партенита в 2009 г. - Телиженко, С.А.; Тесленко, И.Б.; Чабай, В.П. (Археологічні дослідження в Україні, 2010)
Results of the research in the north-eastern part of Parthenita hill-fort archaeological site in Partenit urban type settlement are presented. Cultural layers, husbandry (pits on a place of a pithos and a pillar) and ritual (necropolis) objects of the 10th and 11th centuries and the 14th and 15th centuries were studied. A fragment of the mediaeval bone stylus should be noted among special finds.